Activation of waste paper: Influence of varied chemical agents on product properties. (1st June 2022) - Inkoua, Stelgen; Li, Chao; Kontchouo, Félix Mérimé Bkangmo; Sun, Kai; Zhang, Shu; Gholizadeh, Mortaza; Wang, Yi; Hu, Xun
Graphical abstract: Scheme 1. Schematic illustration of the procedures for activation of WP. Highlights: Activating WP with K2 C2 O4, H3 PO4 or ZnCl2 forms products of distinct nature. H3 PO4 /ZnCl2 catalyzes formed more bio-oil but less gas, and K2 C2 O4 is opposite. K2 C2 O4 and ZnCl2 are more effective than H3 PO4 for creating pores from WP. ZnCl2 creates abundant macropores via converting fibers in WP to graphitic crystals. K2 C2 O4 shows lower environmental impact than ZnCl2 in activating WP. Abstract: Waste paper (WP) is rich in cellulose, which can be activated to produce porous carbon, bio-oil, and combustible gases. During chemical activation of WP, the use of varied chemical agents not only generates activated carbon of distinct pore structure but also bio-oil/gases of different property. In this study, the activation of WP with varied chemical agents was conducted. The distinct characteristics of activated carbon and also bio-oil/gases were correlated with the different nature of the used chemical agents. The results indicated that H3 PO4 and ZnCl2 catalyzed polymerization reactions for producing more bio-oil while less gases owing to their Brønsted and Lewis acidic sites. K2 C2 O4 showed high activity for cracking/gasification reactions, forming bio-oil with higher abundance of organics with smaller π-conjugated structures. In addition, ZnCl2 could create a very coarse porous structure with abundant macropores via destroying fiber structure in WP and promoting the growth of graphitic crystals. In comparison, K2 C2 O4 hindered the aromatization and facilitated the formation of amorphous activated carbon. K2 C2 O4 and ZnCl2 were much more effective than H3 PO4 for creating micropores and mesopores from WP, the derived activated carbon showed superior performances as the electrode of supercapacitor and adsorbent for adsorption of oxytetracycline from aqueous solution. In addition, K2 C2 O4 as activating agent showed lower environmental impact than ZnCl2 in terms of energy consumption, environmental pollution and the greenhouse effect.